Concentration-Dependent Impact of Alkali Li Metal Doped Mesoporous TiO2 Electron Transport Layer on the Performance of CH3NH3PbI3 Perovskite Solar Cells - Peter Amalathas, Amalraj; Landová, Lucie; Conrad, Brianna; Holovský, Jakub (Journal of physical chemistry. C, 2019)
TiO2 is most commonly employed as an electron transport layer (ETL) in mesoscopic n–i–p perovskite solar cells (PSCs). However, the low electron mobility, low electrical conductivity, and high electronic trap states of TiO2 may have negative impacts on further enhancement of PSC performance. Metal doping is an efficient way to improve the electronic properties of TiO2 films. In this work, we investigate the concentration-dependent impact of alkali lithium metal doping of the mesoporous TiO2 ETL on the performance of mesoscopic CH3NH3PbI3 PSCs. It was found that Li doping results in remarkable improvement in electrical conductivity and electron mobility and reduces the number of electronic trap states arising due to the oxygen vacancies within TiO2 lattice. Such enhancements led to an enhanced charge extraction and transport and reduced charge recombination rate at the perovskite/mesoporous TiO2 interface as revealed by steady-state photoluminescence (PL) and time-resolved PL (TRPL) spectra, and resulted in an increase in the V OC, J SC, and FF of the PSCs. Moreover, the J–V curve hysteresis behavior after Li doping was effectively suppressed due to the reduced charge accumulation and recombination at the TiO2/perovskite interface. Consequently, the device performance relies on the concentration of alkali lithium metal doping, and the power conversion efficiency (PCE) of the PSC was significantly improved from 13.64% to 17.59% with reduced the J–V curve hysteresis behavior for a Li doped mesoporous TiO2 layer with an optimized concentration of 30 mg/mL.